A Gibbs sampling method to determine biomarkers for asthma. (April 2017) - Huang, Zhi-Jian; Shen, Qin-Hai; Wu, Yan-Sheng; Huang, Ya-Li
Graphical abstract: Highlights: Totally, 5 differentially expressed MF were acquired according to alfa.pi > 0.6. 338 co-expressed genes were gained. Ubiquitin mediated proteolysis included maximum numbers of 35 co-expressed genes. Cell cycle were enriched by the second largest number of 11 co-expressed genes. Abstract: Purpose: To identify potential biomarkers and to uncover the mechanisms underlying asthma based on Gibbs sampling. Methods: The molecular functions (MFs) with genes greater than 5 were determined using AnnotationMFGO of BAGS package, and the obtained MFs were then transformed to Markov chain (MC). Gibbs sampling was conducted to obtain a new MC. Meanwhile, the average probabilities of MFs were computed via MC Monte Carlo (MCMC) algorithm, followed by identification of differentially expressed MFs based on the probabilities of MF more than 0.6. Moreover, the differentially expressed genes (DEGs) and their correlated genes were screened and merged, called as co-expressed genes. Pathways enrichment analysis was implemented for the co-expressed genes. Results: Based on the gene set more than 5, overall 396 MFs were determined. After Gibbs sampling, 5 differentially expressed MF were acquired according to alfa.pi > 0.6. Moreover, the genes in these 5 differentially expressed MF were merged, and 110 DEGs were identified. Subsequently, 338 co-expressed genes were gained. Based on the P value < 0.01, the co-expressed genes were significantly enriched in 6 pathways. Among these, ubiquitin mediated proteolysis contained the maximum numbers of 35 co-expressed genes, and cell cycle were enriched by the second largest number of 11 co-expressed genes, respectively. Conclusions: The identified pathways such as ubiquitin mediated proteolysis and cell cycle might play important roles in the development of asthma and may be useful for developing the credible therapeutic approaches for diagnosis and treatment of asthma in future.